The Fed speaks, but does the press repeat? Investigating the communication channel between the Fed and the written press - Ami Dalloul (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2024)
This paper investigates the effectiveness of the media transmission channel of the Federal Reserve (Fed) communication with the general public. Spanning a 20-year period (2003-2023), around 5,400 Fed communication documents and 333,000 articles from USA Today are analyzed. A positive and significant relationship between Fed communications and media coverage is found, particularly after the introduction of post-FOMC press conferences. Crisisrelated topics strongly resonate with the media, while other topics such as inflation forecasts show varied effectiveness. Changes in the Fed's communication style has been effective for topics like inflation, however the effect is not uniform across all Fed communications topics.
Keywords: E52; E58; C55; 330; monetary policy; central bank communication; topic modelling; media transmission channel